2021
DOI: 10.1111/imb.12738
|View full text |Cite
|
Sign up to set email alerts
|

V‐ATPase subunit a is required for survival and midgut development of Locusta migratoria

Abstract: The vacuolar-type H + -ATPase (V-ATPase) is an ATPdependent proton pump, which regulates various cellular processes. To date, most functional studies on V-ATPases of insects have focused on subunits of the V1 complex, and there is little information on the VO genes. In this study, two cDNA sequences of LmV-ATPase a were identified in Locusta migratoria. RT-qPCR analysis revealed that LmV-ATPase a1 and LmV-ATPase a2 are differentially expressed in various tissues and developmental stages. Injection of dsRNA for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Recently, we identi ed V-ATPase as a suspected target of the botanical insecticide Celagulin V (Lu et al 2016;Ding et al 2019). Furthermore, a number of studies on silencing of V-ATPase reinforce its indispensability for insects (Liu et al 2022; Rahmani and Bandani 2021; Shi et al 2022). All the evidences indicate that V-ATPase is an important target for insecticides, which has sparked the enthusiasm for insecticide research using insect V-ATPase as a target (Muench et al 2014;Ding et al 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, we identi ed V-ATPase as a suspected target of the botanical insecticide Celagulin V (Lu et al 2016;Ding et al 2019). Furthermore, a number of studies on silencing of V-ATPase reinforce its indispensability for insects (Liu et al 2022; Rahmani and Bandani 2021; Shi et al 2022). All the evidences indicate that V-ATPase is an important target for insecticides, which has sparked the enthusiasm for insecticide research using insect V-ATPase as a target (Muench et al 2014;Ding et al 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Further effects on the larval development could be expected since, in D. melanogaster, defects in protein biosynthesis as a result of reduction of the expression of ribosomal proteins such as RPS13 leads to the appearance of characteristic phenotypes as larval development delay, poor viability, altered body size, and reduced fertility. 88,89 Vacuolar ATPase silencing in nymphs and larvae reduced their food intake, decreased larval growth, adult development, and emergence, and even increased mortality, 90 probably by affecting the integrity and function of the larval midgut and Malpighian tubules. [91][92][93] However, the detrimental effect of silencing these genes on Ceratitis capitata larvae remain to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…V-ATPase is a class of important transporters that play an important role in plasma membrane proton transport in various cell types and are important for cellular processes ( Wagner et al., 2004 ; Beyenbach and Wieczorek, 2006 ; Forgac, 2007 ; Hinton et al., 2009 ). Studies on many insects, including D. citri , Sphenophorus levis Vaurie, and Locusta migratoria (Linnaeus), have found that the interference of V-ATPase gene will affect the growth and survival of insects ( Mohan et al., 2021 ; Guo et al., 2022 ; Liu et al., 2022 ). Studies have shown that RNAi knockdown of V-ATPase in Monochamus alternatus Hope inhibited the expression of immunity-related genes, including lysozyme , TAK1 , and pelle ( Li et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%